2010
DOI: 10.1037/a0020662
|View full text |Cite
|
Sign up to set email alerts
|

Do different types of school mathematics development depend on different constellations of numerical versus general cognitive abilities?

Abstract: The purpose of this study was to examine the interplay between basic numerical cognition and domain-general abilities (such as working memory) in explaining school mathematics learning. First graders (n=280; 5.77 years) were assessed on 2 types of basic numerical cognition, 8 domain-general abilities, procedural calculations (PCs), and word problems (WPs) in fall and then reassessed on PCs and WPs in spring. Development was indexed via latent change scores, and the interplay between numerical and domain-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
287
7
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 225 publications
(343 citation statements)
references
References 100 publications
35
287
7
9
Order By: Relevance
“…The importance of WM also relies on this construct's good predictive value. Indeed, several studies revealed that WM can be considered a strong predictor of mathematics performance in simple arithmetic (Caviola, Mammarella, Lucangeli, & Cornoldi, 2014;Fuchs et al, 2010), and in arithmetical and geometrical problem solving (Giofrè, Mammarella, Ronconi, & Cornoldi, 2013;Passolunghi, Mammarella, & Altoè, 2008). In addition, WM impairments have been demonstrated in participants with DD (Krajewksi, & Schneider, 2009;Mammarella, Caviola, Lucangeli, & Cornoldi, 2013;Passolunghi & Siegel, 2001;Schuchardt, Maehler, & Hasselhorn, 2008).…”
Section: Running Head: Separating Math From Anxietymentioning
confidence: 99%
“…The importance of WM also relies on this construct's good predictive value. Indeed, several studies revealed that WM can be considered a strong predictor of mathematics performance in simple arithmetic (Caviola, Mammarella, Lucangeli, & Cornoldi, 2014;Fuchs et al, 2010), and in arithmetical and geometrical problem solving (Giofrè, Mammarella, Ronconi, & Cornoldi, 2013;Passolunghi, Mammarella, & Altoè, 2008). In addition, WM impairments have been demonstrated in participants with DD (Krajewksi, & Schneider, 2009;Mammarella, Caviola, Lucangeli, & Cornoldi, 2013;Passolunghi & Siegel, 2001;Schuchardt, Maehler, & Hasselhorn, 2008).…”
Section: Running Head: Separating Math From Anxietymentioning
confidence: 99%
“…Children transition from these automatic, basic quantitative competencies (biological evolution-based; Geary, 2007) to formal, complex mathematical competencies (culturally-based), such as counting words (vocabulary), Arabic numerals, the decimal system, and the rest of mathematical theory through broad, domain-general cognitive processes, including reasoning, language, memory, visual and auditory processes, among others (Geary, Hoard, Nugent, & Byrd-Craven, 2008). However, the specific contribution of broad cognitive processes on mathematics achievement is not clearly understood, particularly from a developmental perspective (Fuchs et al, 2010).…”
Section: Domain Specific Cognitive Processesmentioning
confidence: 99%
“…Visual-spatial processing (as a component of working memory, or as an independent cognitive process) remains a factor theorized to support basic calculation skills, as well as advanced mathematics and geometry; however, empirical evidence is lacking or contradictory (Geary, 1993;Fuchs et al, 2010;McGrew & Wendling, 2010). From an evolutionary perspective, visual-spatial cognitive processes probably precede auditory cognitive processes, and they are most likely highly elaborated and robust given the importance of visual information for primates.…”
Section: Broad Cognitive Processesmentioning
confidence: 99%
See 2 more Smart Citations